Pengaruh Intellectual Capital Terhadap Tax Avoidance Pada Perusahaan Subsektor Perbankan Di Bursa Efek Indonesia - Karisma Oktavia; Moh. Danang Bachtiar (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Every company that earns income has an obligation to pay taxes to the state treasury. However, this is not in accordance with the company's goal of obtaining maximum profits. So companies make tax avoidance efforts to minimize taxes by utilizing resources in the form of intellectual capital. This research aims to determine the influence of Intellectual Capital on Tax Avoidance in banking subsector companies. The sampling technique used was a saturated sample so that 47 banking companies were obtained with the observation year 2019-2022. Using multiple linear regression analysis, the results show that intellectual capital has an effect on tax avoidance, human capital and structural capital have no effect on tax avoidance, capital employed has an effect on tax avoidance.